Stages and Processes of Change Utilized by Female Sex Workers Participating in an Alcohol-Reduction Intervention in Mombasa, Kenya. (10th November 2015) - Velloza, Jennifer; L'Engle, Kelly; Mwarogo, Peter; Chokwe, Jackie; Magaria, Loice; Sinkele, William; Kingola, Nzioki
Abstract : Background : According to the transtheoretical model (TTM) behavior change occurs through a series of steps when an individual becomes aware of a behavior, prepares to change, and executes those changes using certain processes. This model has not yet been used to describe alcohol-reduction behavior change processes in resource-limited settings. Objective : This qualitative analysis aimed to describe and characterize the stages and processes of change employed by female sex workers in Mombasa, Kenya during the course of their participation in a 6-month alcohol reduction intervention. Methods : In 2011–2012, clinical interviews were conducted with 45 female sex workers. One interview was conducted each month during the intervention period, resulting in a total of six transcripts per participant. During each interview, the counselor noted the participant's stage of change and recent alcohol use. The clinical notes were analyzed via qualitative coding techniques and organized into matrices to classify alcohol reduction strategies discussed by participants. Results : Participants discussed using the stage-specific processes of change described by the TTM to reduce their alcohol use and maintain the behavior change. Participants who were HIV-positive at the start of the intervention seemed to progress to the action/maintenance stage more quickly than HIV-negative participants. Conclusions/Importance : Results suggest that the TTM constructs may be relevant in understanding the alcohol reduction behavior change process of an at-risk population in a resource-limited setting. Future quantitative research should seek to validate the TTM's application internationally. Alcohol interventions should consider tailoring content to participants' stages of change and HIV-status for increased effectiveness.